Systematics, biogeography and morphological evolution in Entosthodon Schwägr. (Bryopsida, Funariaceae) with a revision of the genus in Africa - Wilding, Nicholas (Department of Biological Sciences, 2016)
Entosthodon Schwägr. (Funariaceae) is a genus of soil-inhabiting, annual to biennial mosses occurring worldwide in temperate to tropical-montane climates. Although a number of regional revisions and treatments exist for the genus, in many parts of the world, it remains poorly known. This is perhaps especially true in Africa, where the identities of most species names are obscure. Furthermore, recent work on the Funariaceae suggests that the sporophytes, long used as the main basis for classification and identification in the group, exhibit high levels of homoplasy and that Entosthodon is paraphyletic as currently circumscribed. I further test the monophyly of Entosthodon, and its relationships to other members of the Funarioideae, through phylogenetic analysis of DNA sequences from four chloroplast regions. These analyses included 45 Entosthodon species (ca. 50 % of those currently recognised), as well as an additional 22 species comprising representatives of all genera of the subfamily (except the rare, monotypic genera Cygnicollum, Clavitheca, Nanomitrella and Brachymeniopsis and the recently described monotypic Afoninia). Bayesian analyses of these data strongly contradict the monophyly of Entosthodon, and it is instead resolved as paraphyletic to a large clade comprising mostly members of Physcomitrium and Physcomitrella. Within this grade, five well supported lineages are resolved - the first comprises 3 species of Entosthodon and is sister to the second lineage, the monotypic Physcomitrellopsis. The third is sister to the afore mentioned i clades and comprises 11 species of Entosthodon within which the monotypic genus Funariella is embedded. The fourth lineage comprises 7 species of Entosthodon and is sister to a clade within which a Physcomitrium-Physcomitrella group is sister to the fifth lineage - a large clade comprising 24 species of Entosthodon. Entosthodon hungaricus is shown to belong in the Physcomitrium clade instead, consistent with its rostrate operculum. Based on the phylogeny, a new classification of Entosthodon sensu lato is proposed. The genus is split into 4 genera (Amphoritheca, Fifeobryum gen nov., Funariella and Entosthodon sens. str.) and the monophyletic Physcomitrellopsis is also maintained. Because of a lack of diagnostic morphological taxonomic characters this new classification is based largely on the molecular circumscription of clades. Nonetheless, particular character combinations do largely characterise most of these genera, albeit that frequent reversals render particular character states non-diagnostic. A revision of these five genera for Africa results in the recognition of twentysix species in total: three in Amphoritheca, 12 in Entosthodon, one in Physcomitrellopsis, one in Fifeobryum, and nine in Funariella. Six of these species, 4 in Entosthodon and 2 in Funariella, are newly described based on specimens from East and southern Africa. A key to the sub-Saharan species is provided, and each is fully described, mapped and illustrated.